Preclinical evaluation of a candidate naked plasmid DNA vaccine against SARS-CoV-2 - Lassaunière, Ria; Polacek, Charlotta; Gram, Gregers J.; Frische, Anders; Tingstedt, Jeanette Linnea; Krüger, Maren; Dorner, Brigitte G.; Cook, Anthony; Brown, Renita; Orekov, Tatyana; Putmon-Taylor, Tammy; Campbell, Tracey-Ann; et al. (npj vaccines, 2021)
New generation plasmid DNA vaccines may be a safe, fast and simple emergency vaccine platform for preparedness against emerging viral pathogens. Applying platform optimization strategies, we tested the pre-clinical immunogenicity and protective effect of a candidate DNA plasmid vaccine specific for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The DNA vaccine induced spike-specific binding IgG and neutralizing antibodies in mice, rabbits, and rhesus macaques together with robust Th1 dominant cellular responses in small animals. Intradermal and intramuscular needle-free administration of the DNA vaccine yielded comparable immune responses. In a vaccination-challenge study of rhesus macaques, the vaccine demonstrated protection from viral replication in the lungs following intranasal and intratracheal inoculation with SARS-CoV-2. In conclusion, the candidate plasmid DNA vaccine encoding the SARS-CoV-2 spike protein is immunogenic in different models and confers protection against lung infection in nonhuman primates. Further evaluation of this DNA vaccine candidate in clinical trials is warranted.